A new vibration isolator integrating tunable stiffness-damping and active driving properties based on radial-chains magnetorheological elastomer. (15th January 2023) - Lin, Dezhao; Yang, Fan; Gong, Di; Li, Ruihong
Graphical abstract: Highlights: Novel vibration isolator designed based on MRE material with radial-chain arrangement. MRE isolator integrating both tunable stiffness-damping and active driving properties. Hyperbolic Hysteresis model predicts the dynamic property of MRE isolator effectively. Large tunable range of working frequency bandwidth subjected to the applied current. Driving 78 times self-weight mass under fluctuation current input with 10Hz frequency. Abstract: In this study, a new vibration isolator integrating tunable stiffness-damping and active driving properties based on Magnetorheological Elastomer (MRE) embedding radial iron chains is proposed. Displacement/base excitations and periodic fluctuation current tests have been utilized to illustrate the fundamental dynamic properties and function of the proposed MRE vibration isolator. The force–displacement/velocity characteristics under different amplitudes/frequencies/currents input show the significant tunable range of the stiffness and damping and hysteresis loop area under the displacement excitation test, which is also described by the established Hyperbolic hysteresis model. Under the base excitation test with the sweep sinusoidal acceleration signals, it has been shown that the transmission properties can be adjusted by the applied current, and has a significant dependency on the amplitude of the acceleration excitation due to the Payne effect. Finally, it has been illustrated that the MRE component can drive a mass of 78 times self-weight in a 10 Hz excitation frequency under the periodic fluctuation current input. Therefore, the adjustable stiffness-damping and active driving force properties of the MRE material itself make the proposed MRE vibration isolator show great application potential in the passive, semi-active and active vibration control area with the fail-safe property.